Digital Technology to Deliver a Lifestyle-Integrated Exercise Intervention in Young Seniors—The PreventIT Feasibility Randomized Controlled Trial - Taraldsen, Kristin; Mikolaizak, A. Stefanie; Maier, Andrea B.; Mellone, Sabato; Boulton, Elisabeth; Aminian, Kamiar; Becker, Clemens; Chiari, Lorenzo; Follestad, Turid; Gannon, Brenda; Paraschiv-Ionescu, Aniosora; Pijnappels, Mirjam; et al. (Frontiers in Digital Health, 2020)
Background: Behavioural change is the key to alter individuals’ lifestyle from sedentary to active. The aim was to assess the feasibility of delivering a Lifestyle-integrated Functional Exercise programme and evaluate the delivery of the intervention by use of digital technology (eLiFE) to prevent functional decline in 61-70-year-old adults. Methods: This multicentre, feasibility randomised controlled trial was run in three countries (Norway, Germany, and the Netherlands). Out of 7500 potential participants, 926 seniors (12%) were screened and 180 participants randomised to eLiFE (n=61), aLiFE (n=59), and control group (n=60). eLiFE participants used an application on smartphones and smartwatches while aLiFE participants used traditional paper-based versions of the same lifestyle-integrated exercise intervention. Participants were followed for 12 months, with assessments at baseline, after a six-month active trainer-supported intervention, and after a further six months of unsupervised continuation of the programme. Results: At 6 months, 87% of participants completed post-test, and 77% completed the final assessment at 12 months. Participants were willing to be part of the programme, with compliance and reported adherence relatively high. Despite small errors during start-up in the technological component, intervention delivery by use of technology appeared acceptable. No serious adverse events were related to the interventions. All groups improved regarding clinical outcomes over time, and complexity metrics show potential as outcome measure in young seniors. Conclusion: This feasibility RCT provides evidence that an ICT-based lifestyle-integrated exercise intervention, focusing on behavioural change, is feasible and safe for young seniors. Trial registration: ClinicalTrials.gov, NCT03065088. Registered on 14 February 2017.